Effects of Rootstock on Grapevine Performance, Petiole and Must Composition, and Overall Wine Score of Vitis vinifera cv. Chardonnay and Pinot noir - Wooldridge, J.; Louw, P.J.E.; Conradie, W.J. (South African Journal of Enology and Viticulture, 2016)
Characteristics of Chardonnay and Pinot noir vines on Richter 99 (99R), Richter 110 (110R), Ruggeri 140 (140Ru) and SO4 rootstocks were assessed over six consecutive seasons in a factorial field trial on an Avalon soil in Stellenbosch that had been limed to pH 5.75 (1M KCl). Ruggeri 140 promoted the highest cane mass (vigour), highest petiole and must nitrogen (N), lowest ratio of yield to cane mass, and lowest overall wine quality. The lowest cane mass and highest wine quality were produced by vines on 110R. Petiole N, phosphorus (P), calcium (Ca) and magnesium (Mg), and must N and Ca, were also lower for vines on 110R than for those on 140Ru.